Hypertensive patients' knowledge of cardiovascular disease on in Calabar, Nigeria - Ogban Omoronyia; Agam Ayuk; Kenneth Nwafor; Annette Legogie (SpringerOpen, 2020)
Abstract Background This study aimed at assessing knowledge of cardiovascular disease risk factors and prevention, among hypertensive patients in a developing country setting with high cardiometabolic disease morbidity and mortality. Methods Using descriptive cross-sectional study design and random sampling method, a 30-item questionnaire was used to obtain quantitative data on knowledge of key aspects of cardiovascular disease and practice of preventive measures among hypertensive patients in Calabar. Result Two hundred and twelve (212) respondents were surveyed with mean age of 45.5 ± 10.8 years. Approximately two-thirds of respondents (67.9%) had unsatisfactory level of knowledge of CVD. Most respondents had unsatisfactory level of knowledge of appropriate diet (77.4%), basic epidemiology (80.2%), risk factors (63.2%), and symptoms of CVD (74.5%). The mean score for knowledge of risk factors was significantly higher among females compared with males (p < 0.05). Consumers compared with non-consumers of alcohol had significantly lower mean scores for knowledge of appropriate diet and symptoms of CVD (p < 0.05). Except for medical knowledge where mean score of knowledge was significantly higher among respondents occasionally exercised or consumed fresh fruits compared with other groups, there was no significant difference in mean score of knowledge for other components comparing the various categories of active exercise and consumption of fresh fruits (p > 0.05). Conclusion Unsatisfactory level of knowledge of cardiovascular disease among hypertensive patients in the study setting was high. There is urgent need to improve efforts and strategies for health education and counseling of patients toward sustainable adoption of preventive behaviors.